Improving irrigation water productivity using Tensiometers - BHATT, RAJAN; ARORA, SANJAY; CHEW, CLARA C. (Journal of Soil and Water Conservation, 2020)
Tensiometer-an instrument which delineate time of applying irrigation water perhaps cheapest, simple and reliable in saving irrigation water amounts and thus in improve the water use efficiency. In the current scenario of water shortage, scientists are busy in find out the ways to improve the water use efficiency. Among the whole world, conditions are somewhat more serious in countries like India because of its agricultural backgrounds. The story is more severe in states where rice is the major kharif crop viz. Punjab, Haryana, Uttar Pradesh etc. The current indigenous practice of flood irrigation to field crops is both injudicious and energy inefficient which leads to lower water productivity. Declining water productivity and low water table are the major problems that stand in front of agricultural scientists as additional water of worth Rs. 2500 million withdrawn every year only in Punjab. Thus, there is a need to look into detail benefits of the tensiometers in terms of water use efficiency, productivity and grain yields terms throughout the world under texturally divergent soils under different agroclimatic conditions. In the present review, attempts had been made as per published literature to check tensiometers performance and our reviewed data delineate that tensiometers in the region result in saving of 11 – 31% of water and 52 – 127 Kwh acre-1 of power without putting much adverse effect on the grains and thus overall improving the water productivity. Finally, we reached at the conclusion that tensiometer works but still it needs to be tested on the long term basis for ranking among different resource conservation technology